Examining impact factors of residential electricity consumption in Taiwan using index decomposition analysis based on end-use level data. (15th December 2020) - Huang, Yun-Hsun
Abstract: The residential sector is the third largest electricity user in Taiwan. A clear understanding of the rapid growth in its electricity consumption is crucial to the formulation of policy. This study applied the Logarithmic Mean Divisia Index (LMDI) to a decomposition of Taiwan's residential electricity consumption based on eighteen electrical appliances. Data was obtained from questionnaire surveys conducted in 7677 households. Note that this study was conducted at various disaggregation levels in order to characterize the consumption of electricity in terms of the factors that contribute to specific end-uses. Climate was identified as the primary factor driving growth in the residential electricity consumption, accounting for an increase of 2.03 billion kWh between 2014 and 2017. In Taiwan, climatic effects manifest primarily as a substantial increase in the use of air-conditioners for cooling. Thus, efforts should be made to accelerate the replacement of low energy-efficiency air conditioners. The same methods could also be used to promote energy upgrades in existing buildings. Our analysis of specific end-uses revealed that the inefficiency of personal computers and dehumidifiers is an important factor in residential electricity consumption. Thus, minimum energy performance standards (MEPS) should be expanded to include these appliances. Highlights: This study identified factors influencing electricity consumption in the residential sector. The electricity consumption for specific end-uses is decomposed into corresponding factors. Contribution from climate effect is investigated by considering cooling degree days. Four policy implications are proposed by analyzing the driving factors in depth.